Preparation method and application of ternary transition metal oxide nano-stained paper-based sensing material

By using Co-Zn-Ni ternary transition metal oxide nanoflowers as capture agents in paper-based sensing materials, combining HRP antibodies and TMB color developer, the problems of high antibody dependence and low detection sensitivity in the prior art are solved, and rapid, sensitive and low-cost detection of Staphylococcus aureus are achieved.

CN119706966APending Publication Date: 2025-03-28洛兮生命科技(杭州)有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411908255.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing paper-based immunochromatography methods rely on antibodies as capture agents when detecting Staphylococcus aureus, resulting in high detection costs and complex antibody pairing and coupling, and it is difficult to improve the sensitivity and stability of the detection.

Method used

The ternary transition metal oxide nanoflower material is used as the capture agent. By adding Co-Zn-Ni ternary transition metal oxide nanoflower to the paper-based sensing material, combining HRP antibodies and TMB color developer, rapid and sensitive detection of Staphylococcus aureus is achieved.

Benefits of technology

It reduces the detection cost, simplifies the detection process, improves the detection sensitivity and stability, and is suitable for rapid screening and detection of large numbers of samples.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706966A_ABST
    Figure CN119706966A_ABST
Patent Text Reader

Abstract

The invention provides an innovative preparation method and application of a ternary transition metal oxide nano-stained paper-based sensing material. The method comprises the following steps: dissolving CoCl2. 6H2O, ZnCl2 and NiCl2. 6H2O in a specific molar ratio in glycerol to form a water phase, mixing the water phase with an oil phase formed by an F127 surfactant, adjusting the pH value by ammonia water, calcining and the like to prepare the nanoflower material. The material has a large specific surface area and excellent bacterial adsorption capacity, and can efficiently capture staphylococcus aureus. In combination with an HRP anti-staphylococcus aureus antibody and a TMB chromogenic reaction, the paper-based sensor constructed by the invention realizes rapid and sensitive detection of staphylococcus aureus. According to the method, a traditional antibody capturing agent is abandoned, the detection cost is reduced, and meanwhile, high specificity and stability are kept. Experimental results show that the paper-based sensor and the staphylococcus aureus concentration logarithm are in a good linear relationship, the detection limit is low, the responsivity to interfering bacteria is low, and the paper-based sensor has good selectivity and practicability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nanometer sensing, and particularly relates to a preparation method and application of a ternary transition metal oxide nano-flower paper-based sensing material. Background Art

[0002] As an important infectious pathogen, Staphylococcus aureus plays an important role in the diagnosis and prevention of infectious diseases. In order to effectively improve the accuracy and timeliness of infectious disease diagnosis, rapid, accurate and highly sensitive detection methods are particularly critical. In recent years, immunochromatography, as an innovative immunoassay technology, has shown broad application prospects in the detection of infectious disease pathogens such as Staphylococcus aureus. This method can not only improve the accuracy of diagnosis, but also provide strong support for the timely prevention and control of infectious diseases.

[0003] The immunochromatography method is based on the principle of specific binding between antigens and antibodies. By fixing specific antibodies on carriers such as nitrocellulose membranes, the capillary action is used to bind the microorganisms (such as bacteria, viruses, etc.) in the sample to be tested to the antibodies. After binding, the presence and concentration of microorganisms are determined by the color change or electrochemical signal of the marker (such as colloidal gold, enzymes, etc.). The current paper-based immunochromatography method has shown significant advantages in environmental monitoring, clinical diagnosis and other fields, but it generally relies on antibodies as capture agents, which not only increases the detection cost, but is also limited by the complexity of antibody pairing and coupling. Therefore, the development of new capture agents has become the key to improving detection efficiency and reducing costs.

[0004] Metal oxides are an important class of inorganic materials. Due to their unique physicochemical properties, they have received extensive attention in the field of catalysis. Among them, transition metal oxides are often used as catalysts or catalyst carriers, showing excellent activity, selectivity and stability in chemical reactions. Their catalytic performance originates from the unfilled d orbitals of transition metal elements, which can accept or provide electrons to promote the activation and conversion of reactants. Some metal oxides exhibit catalytic properties similar to nanozymes, which enable them to catalyze a variety of chemical reactions under mild conditions; in addition to catalytic properties, metal oxides also have the ability to non-specifically adsorb bacteria, which is mainly due to the physicochemical properties of the metal oxide surface, such as charge distribution, hydrophilicity and hydrophobicity, and surface defects. However, when trying to integrate metal oxides into paper-based sensing material systems to achieve effective detection of bacteria, current technologies still face some challenges, such as: how to prepare ternary transition metal oxide nanoflowers with excellent bacterial adsorption capacity to ensure efficient interaction with target bacteria; at the same time, how to improve the sensitivity and stability of this paper-based sensing material during the detection process is also an urgent problem to be solved. Summary of the invention

[0005] Based on the above technical problems, the present invention proposes an innovative preparation method and application of ternary transition metal oxide nanoflower paper-based sensing materials, which is achieved through the following technical solutions:

[0006] Preparation of S1 ternary transition metal oxide nanoflowers: According to CoCl 2 6H 2 O、ZnCl 2 、NiCl 2 6H 2 O molar ratio X:Y:Z, CoCl 2 6H 2 O、ZnCl 2 、NiCl 2 6H 2 1L glycerol was dissolved in 1L glycerol to form a uniform aqueous solution; 10g F127 surfactant was weighed and dissolved in 1L DMSO to form a uniform oil solution. The above metal ion solution (aqueous phase) and surfactant solution (oil phase) were mixed in equal proportions and stirred at a speed of 600 rpm on a magnetic stirrer for 20 minutes. NH 3 ·H 2 O to adjust the pH to 8.6, continue stirring for 2 hours, and place the reacted solution under N 2 The sample was protected and calcined at 550℃ for 2h at a heating rate of 5℃ / min to remove the template F127, glycerol and DMSO. After the reaction, the sample was cooled to room temperature naturally, and the obtained product was repeatedly washed with deionized water and filtered three times, and finally dispersed with anhydrous ethanol. Finally, the product was placed in an oven and dried to constant weight to obtain Co-Zn-Ni ternary transition metal oxide nanoflower materials with different molar ratios.

[0007] Preparation of S2 paper-based sensor: Cut Whatman filter paper into 20mm×15mm size, evenly coat 1mg / mL HRP anti-Staphylococcus aureus antibody on the surface of Whatman filter paper, place it on a sterile operating table, and dry it naturally at room temperature for 2h. Then, add 5μL of 15mM TMB ethanol solution to the dried filter paper surface, and wait for ethanol to evaporate until the filter paper is dry at room temperature.

[0008] S3 immunochromatographic detection: Co-Zn-Ni ternary transition metal oxide nanoflowers were directly added to Staphylococcus aureus suspensions of different concentrations (0-10 8 CFU / mL), fully mixed and incubated for 5 minutes. Then 3 μL of the mixed reaction solution was dropped on the surface of the paper-based sensor, and the detection area was observed after 20 minutes.

[0009] Preferably, in the ternary transition metal oxide nanoflower composite material prepared in step S1, the molar ratio of Co, Zn and Ni is X:Y:Z, wherein X, Y and Z are the molar ratios of Co, Zn and Ni respectively, and X+Y+Z=1.

[0010] Preferably, the molar ratio of X is in the range of 0.4-0.6 mol, the molar ratio of Y is in the range of 0.1-0.35 mol, and the molar ratio of Z is in the range of 0.2-0.5 mol.

[0011] Beneficial effects of the present invention:

[0012] The present invention first prepares a ternary transition metal oxide nanoflower containing three transition metals, Co, Zn, and Ni, which has a large specific surface area and can capture bacteria in all directions. In addition, the present invention abandons the capture antibody that is indispensable in the traditional paper-based immunochromatography method, thereby greatly reducing the detection cost - through the combination of HRP anti-Staphylococcus aureus antibody on the immunochromatography test paper and Staphylococcus aureus, specific detection of Staphylococcus aureus is achieved, and by coupling HRP, catalyzing and amplifying the color development reaction of TMB, rapid and sensitive detection of Staphylococcus aureus is achieved, without the need for cumbersome antibody pairing and coupling processes. The ternary transition metal oxide nanoflower paper-based sensing material prepared by the present invention has the advantages of simple operation, reliable results, high efficiency, etc., and is suitable for rapid screening and detection of a large number of samples. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 The morphology characterization results of Co-Zn-Ni ternary transition metal oxide nanoflower materials; Figure 1 a is the SEM characterization result of the prepared Co-Zn-Ni (0.6:0.2:0.2) ternary transition metal oxide nanoflowers. Figure 1 b is the SEM characterization result of the prepared Co-Zn-Ni (0.4:0.1:0.5) ternary transition metal oxide nanoflowers. Figure 1 c is the SEM characterization result of the prepared Co-Zn-Ni (0.45:0.35:0.2) ternary transition metal oxide nanoflowers, scale bar 100 nm.

[0014] Figure 2 This is the adsorption-desorption curve of Co-Zn-Ni ternary transition metal oxide nanoflower material; Figure 2 a is the BET analysis result of the prepared Co-Zn-Ni (0.6:0.2:0.2) ternary transition metal oxide nanoflowers. Figure 2 b is the BET analysis result of the prepared Co-Zn-Ni (0.4:0.1:0.5) ternary transition metal oxide nanoflowers. Figure 2c is the BET analysis result of the prepared Co-Zn-Ni (0.45:0.35:0.2) ternary transition metal oxide nanoflowers.

[0015] Figure 3 Characterization results of the performance of Co-Zn-Ni ternary transition metal oxide nanoflower materials in capturing Staphylococcus aureus; Figure 3 a is the TEM characterization result of Staphylococcus aureus, Figure 3 b is the TEM characterization result of Co-Zn-Ni (0.4:0.1:0.5) ternary transition metal oxide nanoflowers capturing Staphylococcus aureus, scale bar: 0.5 μm.

[0016] Figure 4 The experimental results of the oxidase catalytic performance of Co-Zn-Ni ternary transition metal oxide nanoflowers; Figure 4 a is the UV-visible absorption spectra of Co-Zn-Ni NFs, Co-Zn-Ni NFs-TMB and TMB; Figure 4 b is the oxidase-like activity at different Co-Zn-Ni NFs concentrations; Figure 4 c Nanozyme activity of Co-Zn-Ni NFs before and after binding with Staphylococcus aureus; Figure 4 d is the absorbance of TMB catalyzed by Co-Zn-Ni NFs at different temperatures.

[0017] Figure 5 The paper-based sensor prepared by the present invention has detection performance in detecting Staphylococcus aureus.

[0018] Figure 6 The specific results of the paper-based sensor prepared in the present invention to Staphylococcus aureus.

[0019] Figure 7 The stability results of the paper-based sensor prepared in the present invention against Staphylococcus aureus. DETAILED DESCRIPTION

[0020] The technical solution proposed in the present invention is further described below in conjunction with the embodiments, but it is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention shall be included in the protection scope of the present invention. Unless otherwise specified in the following embodiments, the technical means used in the embodiments of the present invention are conventional means well known to those skilled in the art.

[0021] Example 1: Preparation of transition metal oxide nanosheets

[0022] Sample 1: 0.6 mol CoCl 2 6H 2 O, 0.2 mol ZnCl2 、0.2molNiCl 2 6H 2 1L glycerol was dissolved in 1L glycerol to form a uniform mixed solution (water phase); 10g F127 surfactant was weighed and dissolved in 1L DMSO to form a uniform mixed solution (oil phase). The above water phase and oil phase were mixed in equal proportions and stirred at a speed of 600 rpm on a magnetic stirrer for 20 minutes. NH 3 ·H 2 O to adjust the pH to 8.6, continue stirring for 2 hours, and place the reacted solution under N 2 The sample was protected and calcined at 550℃ for 2h at a heating rate of 5℃ / min to remove the template F127, glycerol and DMSO. After the reaction, the sample was cooled to room temperature naturally, and the obtained product was repeatedly washed with deionized water and filtered three times, and finally dispersed with anhydrous ethanol. Finally, the product was placed in a constant temperature drying oven and dried to constant weight to obtain Co-Zn-Ni (0.6:0.2:0.2) ternary transition metal oxide nanoflower material.

[0023] Sample 2: The difference between this sample and sample 1 is that CoCl 2 6H 2 O、ZnCl 2 、NiCl 2 6H 2 O molar ratio is 0.4:0.1:0.5, and the other preparation processes are the same as sample 1, and finally the Co-Zn-Ni (0.4:0.1:0.5) ternary transition metal oxide nanoflower material is prepared.

[0024] Sample 3: The difference between this sample and sample 1 is that CoCl 2 6H 2 O、ZnCl 2 、NiCl 2 6H 2 O molar ratio is 0.45:0.35:0.2, and the other preparation processes are the same as sample 1, and finally the Co-Zn-Ni (0.45:0.35:0.2) ternary transition metal oxide nanoflower material is prepared.

[0025] Example 2: Characterization of ternary transition metal oxide nanoflowers

[0026] The sample morphology of the three different molar ratios of Co-Zn-Ni ternary transition metal oxide nanoflowers prepared in Example 1 was measured using a scanning electron microscope (SEM, SU8010, Hitachi, Japan). The results are shown in 1. Figure 1 a. Figure 1 b and Figure 1c is the TEM image of sample 1, sample 2 and sample 3 prepared in Example 1, with a diameter of about 500 nm, relatively uniform dispersion, and no obvious aggregation of nanoparticles. It can be seen that these three samples have a layered flower-like morphology, indicating that Co-Zn-Ni nanoflowers with different molar ratios were successfully prepared.

[0027] The N 2 The adsorption-desorption isotherms of the three samples are shown in Figure 2 a. Figure 2 b and Figure 2 As shown in c, the three samples all have similar type IV isotherms, indicating that the surface of the nanoflowers has a mesoporous structure. The specific surface areas of samples 1, 2, and 3 are calculated to be approximately 156 m 2 / g, 164m 2 / g and 123m 2 / g, among which sample 2 has the largest specific surface area and the largest pore size. The Co-Zn-Ni ternary transition metal oxide nanoflowers with this molar ratio (0.4:0.1:0.5) show a higher specific surface area. This property provides more adsorption sites for the transition metal oxide nanoflowers, thereby enhancing the interaction with the surface of Staphylococcus aureus; in addition, the presence of pore size can enhance the interaction between the adsorbed Staphylococcus aureus and the surface of the nanomaterial, thereby improving the adsorption stability. According to the characterization results of Example 2, the Co-Zn-Ni ternary transition metal oxide nanoflowers prepared by Sample 2 are selected for research in the subsequent examples.

[0028] Example 3: Characterization of Staphylococcus aureus captured by ternary transition metal oxide nanoflowers

[0029] According to the characterization results of Example 2, the Co-Zn-Ni ternary transition metal oxide nanoflowers prepared in Sample 2 were selected to investigate the ability to capture Staphylococcus aureus. Figure 3 As shown in a, it showed a regular spherical outline, uniform cytoplasm and smooth and dense surface. Figure 3 a) Compared with the Co-Zn-Ni ternary transition metal oxide nanoflower treatment group, the transmission electron microscopy image shows ( Figure 3 b), the Co-Zn-Ni ternary transition metal oxide nanoflowers prepared by the present invention tightly adhere to the surface of Staphylococcus aureus, indicating that the Co-Zn-Ni NFs have been bound to the surface of Staphylococcus aureus, which may be due to the van der Waals force, electrostatic effect and hydrophobic interaction of the transition metal oxide nanoflowers, indicating that the ternary transition metal oxide nanoflowers prepared by the present invention can achieve successful capture of Staphylococcus aureus.

[0030] Example 4: Oxidase catalytic performance of Co-Zn-Ni ternary transition metal oxide nanoflowers

[0031] (1) Simulation of the oxidase activity of Co-Zn-Ni ternary transition metal nanoflowers: 50 μL Co-Zn-Ni NFs (50 μg / mL) were dispersed in 185 μL HAc-NaAc buffer (10 mM, pH 4.0), which contained 15 μL 20 mM TMB. The final concentration of Co-Zn-Ni NFs was 5 μg / mL. At room temperature, the catalytic performance of Co-Zn-Ni NFs of different concentrations (10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 120 and 140 μg / mL were prepared in the same way, and the concentration was adjusted only by proportionally increasing the amount of initial Co-Zn-Ni NFs added) was detected at a wavelength of 652 nm.

[0032] Figure 4 a shows that Co-Zn-Ni NFs oxidize TMB to produce blue oxidation products, and an obvious absorption peak appears at 650nm. Meanwhile, in the absence of Co-Zn-Ni NFs, TMB is not oxidized, the solution remains colorless, and no absorption peak appears at 652nm. In addition, Figure 4 As shown in (b), as the concentration of Co-Zn-Ni NFs increases, its catalytic performance, i.e., the absorbance of ox-TMB, gradually increases, and the concentration of nanozymes is linearly related to the absorbance. These results indicate that the prepared Co-Zn-Ni NFs have oxidase-like activity, which can catalyze TMB to produce ox-TMB and trigger visual color signals. Figure 4 As shown in (c), the catalytic activity of Co-Zn-Ni NFs did not change significantly before and after binding with Staphylococcus aureus. The above results prove that the oxidase-like Co-Zn-Ni NFs exhibit relatively stable catalytic performance, which is beneficial to the construction of stable Co-Zn-Ni nanozyme-mediated visual biosensor.

[0033] (2) Detection of the oxidase stability of Co-Zn-Ni ternary transition metal nanoflowers: 50 μL Co-Zn-Ni NFs (50 μg / mL) were dispersed in 185 μL HAc-NaAc buffer (10 mM, pH 4.0), which contained 15 μL 20 mM TMB. The final concentration of Co-Zn-Ni NFs was 5 μg / mL. Incubation was carried out at 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C and 80°C. Then 5 μL 15 mM TMB was added to the above mixture and incubated for 5 minutes to evaluate the effect of temperature on catalytic activity.

[0034] like Figure 4 As shown in Figure d, at 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C and 80°C, the absorbance of Co-Zn-NiNFs ternary transition metal nanoflowers as nanozymes did not increase or decrease significantly. This indicates that Co-Zn-Ni NFs are resistant to extreme temperatures, and the catalytic activity does not change significantly in the range of 10 to 80°C, indicating that Co-Zn-Ni NFs nanozymes have stronger temperature tolerance than natural enzymes.

[0035] Example 5: Construction of a paper-based sensor for Staphylococcus aureus detection

[0036] Cut the Whatman filter paper into 20mm×15mm size, evenly coat the surface of the Whatman filter paper with 1mg / mL HRP anti-Staphylococcus aureus antibody, place it on a sterile operating table, and dry it naturally at room temperature for 2h. Then, add 5μL of 15mM TMB ethanol solution to the dried filter paper surface, and wait for the ethanol to evaporate until the filter paper is dry at room temperature.

[0037] Example 6: Detection of Staphylococcus aureus using paper-based sensors

[0038] (1) Prepare the mixture at concentrations of 0, 10, and 10 2 , 10 3 , 10 4 , 10 5 , 10 6 , 10 7 , 10 8 CFU / mL of Staphylococcus aureus suspension was prepared by taking sample 2 Co-Zn-Ni ternary transition metal oxide nanoflowers prepared in Example 1, and adding the Co-Zn-Ni ternary transition metal oxide nanoflowers directly to Staphylococcus aureus suspensions of different concentrations (0-10 8 CFU / mL), fully mixed and incubated for 5 minutes. Then 3 μL of the mixed reaction solution was dropped on the surface of the paper-based sensor. After 20 minutes, the detection area was observed and the color optical density value was analyzed using Image J software. Figure 5 As shown, the paper-based sensor has a good linear relationship with the logarithm of the Staphylococcus aureus concentration, which can be expressed as y=1888.6x-7113.1, with a linear correlation coefficient of 0.9994 and a detection limit of 2 CFU / mL.

[0039] (2) Specificity detection of paper-based sensors: In order to detect the specificity of the paper-based sensors prepared by the present invention, the following strains were used as interferences: Escherichia coli, Pseudomonas aeruginosa, Bacillus subtilis, Enterobacter sakazakii, and Staphylococcus epidermidis. The signal strength of different interfering substances on the paper-based substrate was measured under the same conditions. Figure 6As shown, the paper-based sensor has a low response to interfering bacteria such as Escherichia coli. This is because Escherichia coli, Pseudomonas aeruginosa, Bacillus subtilis, Enterobacter sakazakii, and Staphylococcus epidermidis. Although Co-Zn-Ni NFs are non-specific adsorbed bacteria, the further recognition of HRP anti-Staphylococcus aureus antibodies makes the interfering strains have no obvious signals, indicating that the paper-based sensor prepared by the present invention has good selectivity for Staphylococcus aureus. This is because the present invention uses a nanomaterial-bacteria-antibody sandwich strategy and uses Co-Zn-Ni NFs as a bacterial recognition element to capture the target bacteria-Staphylococcus aureus. In this case, such nanoparticles are usually universal as recognition agents. For this purpose, anti-Staphylococcus aureus mAb is carefully selected and coupled with horseradish peroxidase (HRP) as the second recognition element, which not only retains the high specific recognition ability of monoclonal antibodies to Staphylococcus aureus, but also utilizes the enzymatic catalytic activity of horseradish peroxidase to achieve signal amplification of the target bacteria, thereby improving the sensitivity of detection.

[0040] (3) Stability test of paper-based sensors: The prepared Co-Zn-Ni ternary transition metal oxide nanoflowers were stored at -20°C, 25°C and 60°C for 10 days, and then paper-based sensors were constructed to detect Staphylococcus aureus. Figure 7 As shown, after the Co-Zn-Ni ternary transition metal oxide nanoflowers prepared according to Example 1 were stored for 10 days, the response value to Staphylococcus aureus was still greater than 85% of the initial value, while after being stored at -20°C and 60°C for 10 days, the stability of the paper-based sensor decreased significantly, indicating that the paper-based sensor prepared by the Co-Zn-Ni ternary transition metal oxide nanoflowers has reliable stability at room temperature.

Claims

1. A method for preparing a Co-Zn-Ni ternary transition metal oxide nanoflower material, characterized in that: The following steps are involved: a) dissolving the three salts in 1 L of glycerol in a molar ratio of CoCl2·6H2O, ZnCl2, and NiCl2·6H2O in a ratio of X:Y:Z to form a uniform aqueous solution; b) dissolving 10 g of F127 surfactant in 1 L of acetone to form a uniform oil phase solution; c) mixing the aqueous phase solution and the oil phase solution in equal proportions, and stirring on a magnetic stirrer at a rotation speed of about 600 rpm for 20 minutes; d) Slowly add NH3·H2O to the mixed solution to adjust the pH value to 8.6, and continue stirring for 2 hours; e) placing the reacted solution under N2 protection, heating it to 550°C at a heating rate of 5°C / min and calcining it for 2 hours to remove the template F127, glycerol and acetone; f) After the sample is cooled naturally to room temperature, it is repeatedly washed and filtered three times with deionized water, and then the product is dispersed with anhydrous ethanol; g) The product is placed in a constant temperature drying oven and dried to a constant weight to obtain a Co-Zn-Ni ternary transition metal oxide nanoflower material.

2. The preparation method according to claim 1, characterized in that: The molar ratio of CoCl2·6H2O, ZnCl2 and NiCl2·6H2O is X+Y+Z=1.

3. The preparation method according to claim 1, characterized in that: The molar ratio of X is in the range of 0.4-0.6 mol, the molar ratio of Y is in the range of 0.1-0.35 mol, and the molar ratio of Z is in the range of 0.2-0.5 mol.

4. A detection method for a paper-based sensor based on Co-Zn-Ni ternary transition metal oxide nanoflower material, characterized in that: The method comprises the following steps: a) Cut the Whatman filter paper into 20 mm × 15 mm size; b) evenly coating 1 mg / mL of HRP anti-Staphylococcus aureus antibody on the surface of the cut filter paper; c) Place the filter paper coated with the antibody on a sterile operating table and dry it naturally at room temperature for 2 hours; d) adding 5 μL of 15 mM TMB ethanol solution to the surface of the dried filter paper, and waiting for the ethanol to evaporate at room temperature until the filter paper is dry; e) directly adding the Co-Zn-Ni ternary transition metal oxide nanoflower material to the Staphylococcus aureus suspension of unknown concentration, mixing thoroughly and incubating for 5 minutes; f) taking 3 μL of the mixed reaction solution and dropping it on the surface of the filter paper modified with TMB in step d; g) After 20 minutes of reaction, observe the detection area.

5. The paper-based sensor detection method according to claim 4, characterized in that: Step e) The Co-Zn-Ni ternary transition metal oxide nanoflower material is prepared by the method according to any one of claims 1 to 3.

6. Use of the paper-based sensor according to any one of claims 4 to 5 in detecting Staphylococcus aureus.

7. The use according to claim 6, characterized in that: The paper-based sensor is linearly correlated with Staphylococcus aureus, the linear equation is y=1888.6x-7113.1, the linear correlation coefficient is 0.9994, and the detection limit is 2 CFU / mL.

8. The use according to claim 6, characterized in that: The concentration range of the Staphylococcus aureus suspension detected by the paper-based sensor is 0-10 8 CFU / mL.